2014
DOI: 10.1002/etc.2726
|View full text |Cite
|
Sign up to set email alerts
|

Effects of herbicide‐treated host plants on the development ofMamestra brassicaeL. caterpillars

Abstract: Herbicides are widely used pesticides that affect plants by changing their chemistry. In doing so, herbicides might also influence the quality of plants as food for herbivores. To study the effects of herbicides on host plant quality, 3 plant species (Plantago lanceolata L., P. major L., and Ranunculus acris L.) were treated with sublethal rates of either a sulfonylurea (Atlantis WG, Bayer CropScience) or a glyphosate (Roundup LB Plus, Monsanto) herbicide, and the development of caterpillars of the cabbage mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…Our results are consistent with several other studies that showed that herbicide exposure can affect larval survival and adult lifespan in insects (Burdett et al, 2001; Hahn et al, 2014; Mirande et al, 2010; Russell and Schultz, 2010). For example, sethoxydim causes a 32% decrease in eclosion success of the cabbage butterfly, Pieris rapae , and fluazifop-p-butyl, a 21% reduction (Russell and Schultz, 2010).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with several other studies that showed that herbicide exposure can affect larval survival and adult lifespan in insects (Burdett et al, 2001; Hahn et al, 2014; Mirande et al, 2010; Russell and Schultz, 2010). For example, sethoxydim causes a 32% decrease in eclosion success of the cabbage butterfly, Pieris rapae , and fluazifop-p-butyl, a 21% reduction (Russell and Schultz, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Atrazine accelerates development time, which is consistent with other work showing a change in development time as a result of pesticide exposure (Burdett et al, 2001; Hahn et al, 2014; Mirande et al, 2010; Russell and Schultz, 2010). For example, glyphosphate causes acceleration in development time in the ladybird beetle, Eriopis connexa germar , (Mirande et al, 2010) while both molinate and thiobencard independently lengthen development time of Chironomus tepperi (Burdett et al, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…In the same study, aphid reproduction was also reduced when aphids were reared on plants sprayed by the field dose of glyphosate, indicating systemic effects of the herbicides on the aphids26. Recently, Hahn et al 23. tested two herbicides for possible sub-lethal effects; they applied glyphosate-based Roundup LB Plus and sulfonylurea-based Atlantis AG to three species of host plants to Mamestra brassicae (Linnaeus) caterpillars.…”
mentioning
confidence: 94%
“… 20 reported that aphids became more abundant in glyphosate-treated plots in herbicide-tolerant crops, which might be a consequence of the increased vigour of crop plants released from competition with weeds 19 or a reduction in the associational resistance of crop plants to herbivores due to a disrupted crop-weed interaction underground 21 . Other modes of action of herbicides against herbivorous insects include the direct toxicity of the formulation 22 or the sub-lethal effects of the herbicides caused by the insects feeding on contaminated or modified, less nutritious food 23 . Available studies, however, present mixed results depending on the taxon and the herbicide used 22 23 24 25 26 .…”
mentioning
confidence: 99%
See 1 more Smart Citation